Transcriptome Analysis Identifies Candidate Genes and Pathways Associated With Feed Efficiency in Hu Sheep - Zhang, Deyin; Zhang, Xiaoxue; Li, Fadi; Li, Chong; La, Yongfu; Mo, Futao; Li, Guoze; Zhang, Yukun; Li, Xiaolong; Song, Qizhi; Zhao, Yuan; Wang, Weimin (Frontiers in Genetics, 2019)
In the genetic improvement of livestock and poultry, residual feed intake (RFI) is an important economic trait. However, in sheep, the genetic regulatory mechanisms of RFI are unclear. In the present study, we measured the feed efficiency (FE)-related phenotypes of 137 male Hu lambs, and selected six lambs with very high (n = 3) and very low (n = 3) RFI values and analyzed their liver transcriptomes. A total of 101 differentially expressed genes (DEGs) were identified, of which 40 were upregulated and 61 were downregulated in the Low-RFI group compared with that in the High-RFI group. The downregulated genes were mainly concentrated in immune function pathways, while the upregulated genes were mainly involved in energy metabolism pathways. Two DEGs, ADRA2A (encoding adrenoceptor alpha 2A) and RYR2 (ryanodine receptor 2), were selected as candidate genes for feed efficiency and subjected to single nucleotide polymorphism (SNP) scanning and association analysis. Two synonymous mutations, ADRA2A g.1429 C > A and RYR2 g.1117 A > C, were detected, which were both significantly associated with the feed conversion rate. These findings provide a deeper understanding of the molecular mechanisms regulating feed efficiency, and reveal key genes and genetic variants that could be used to genetically improve feed efficiency in sheep.